2013
DOI: 10.1002/acr.22047
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcomes of Posterior Reversible Encephalopathy Syndrome in Patients With Systemic Lupus Erythematosus

Abstract: Objective. To analyze the clinical features and outcomes of patients with posterior reversible encephalopathy syndrome (PRES), the risk factors of PRES-related intracranial hemorrhage (ICH), and all-cause mortality in patients with systemic lupus erythematosus (SLE). Methods. Twenty-six episodes of PRES were identified in 23 SLE patients, using an electronic medical records database of 3,746 SLE patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
38
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(55 citation statements)
references
References 39 publications
10
38
0
5
Order By: Relevance
“…In agreement with other studies, we found that patients with SLE who develop PRES are younger, have high activity indexes and present with seizures as the main clinical manifestation 21. We also found that PRES episodes happened in the first hours of hospitalisation, regardless of the cause of admission.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with other studies, we found that patients with SLE who develop PRES are younger, have high activity indexes and present with seizures as the main clinical manifestation 21. We also found that PRES episodes happened in the first hours of hospitalisation, regardless of the cause of admission.…”
Section: Discussionsupporting
confidence: 92%
“…Although the prevalence of PRES in patients with SLE has been reported to be less than 1%,21 SLE is the most frequently associated rheumatological disease 14. Aggressive immunosuppressive treatments, high SLEDAI scores, renal dysfunction and uncontrolled hypertension have been previously described as factors related to PRES development in patients with SLE 10 11 13.…”
Section: Discussionmentioning
confidence: 99%
“…8,14 Un 20%-95% de pacientes con LES tienen manifestaciones neurológicas agrupadas bajo la denominación de lupus neuropsiquiátrico (LNPS) y pueden ser la forma de presentación del LES con escasos síntomas sistémicos. 6,15 Las manifestaciones clínicas son similares a la EPR y, por lo tanto, difíciles de diferenciar. Se recomienda el uso de la resonancia magnética para llegar a un diagnóstico de certeza y planear el tratamiento correspondiente.…”
Section: Discussionunclassified
“…[1][2][3]6,7,10,12,14 En conclusión, la EPR debe considerarse una manifestación aguda del LES. El uso de la resonancia magnética en sus diferentes secuencias permite hacer el diagnóstico y descartar otras patologías que engloban el LNPS.…”
Section: Discussionunclassified
See 1 more Smart Citation